BEING A WOMAN IN A MAN'S WORLD:A FEMINIST ANALYSIS ON THE MANIFESTATION OF LOVEIN THE SHORT STORIES BY EDITH WHARTON - Isda Dafitri, - (2009)
The research paper analyzes man and woman relationships in the short stories written by Edith Wharton which are taken as the data for the study. The aim of the study is to find out the answers to the research question: "How do the texts construct the manifestation of love in husband and wife relations?" The study uses a qualitative descriptive approach to answer the formulated research question above. The process begins by applying the close reading strategy in which the short stories are read thoroughly and carefully to determine the main issue of the study and to collect data presentation which are available in the short stories. Afterwards, the data collected in the form of textual evidences are analyzed by means of existentialist feminism which will reveal the manifestation of love in the husband and wife relations. The results of the study indicate that both short stories have reflected the same issue that is the manifestation of love in the marriage. From an existentialist feminist perspective, the form of love presented in the text is not only affection or passion but also resentment and lies. The wife's view and the husband's view about marriage in the stories are investigated to see their relations. This can be seen from the husband and wife's attitudes and their efforts to maintain their marriage.